Glioma Mimics: Magnetic Resonance Imaging Characteristics of Granulomas in Dogs - Diangelo, Lauren; Cohen-Gadol, Aaron; Heng, Hock Gan; Miller, Margaret A.; Hague, Devon W.; Rossmeisl, John H.; Bentley, R. Timothy (Frontiers in Veterinary Science, 2019)
Granulomas can “mimic” gliomas on magnetic resonance imaging (MRI) in human patients. The goal of this retrospective study was to report canine brain granulomas that were consistent with glioma based upon MRI, report their histologic diagnosis, and identify MRI criteria that might be useful to distinguish granuloma from glioma. Ten granulomas, initially suspected to be glioma based on MRI, were ultimately diagnosed as granulomatous meningoencephalomyelitis (n = 5), infectious granulomas (n = 3) or other meningoencephalitis (n = 2). Age was 1.6 to 15.0 years and two dogs were brachycephalic breeds. MRI characteristics overlapping with glioma included intra-axial, heterogeneous, T2-weighted hyperintense, T1-weighted hypointense to isointense mass lesions with contrast-enhancement. Signals on fluid attenuation inversion recovery, gradient echo and diffusion weighted imaging also matched glioma. Peri-lesional edema and mass effect were towards the high end of findings reported for glioma. MRI characteristics that would be considered unusual for glioma included dural contact (n = 4), T2-hypointensity (n = 2), concomitant meningeal-enhancement (n = 9) and minor changes in the contralateral brain (n = 2). Cerebrospinal fluid analysis revealed albuminocytological dissociation or mild pleocytosis. These cases show that granulomas can “mimic” glioma on canine brain MRI. In individual cases, certain MRI findings may help increase the index of suspicion for granuloma. Lack of pronounced cerebrospinal fluid pleocytosis does not exclude granuloma. Signalment is very useful in the suspicion of glioma, and many of these dogs with granuloma were of ages and breeds in which glioma is less commonly seen.